Kinetic modeling for catalytic cracking of pyrolysis oils with VGO in a FCC unit. (12th October 2017) - Naik, Desavath V.; Karthik, Varaha; Kumar, Vimal; Prasad, Basheshwar; Garg, Madhukar O.
Highlights: Catalytic cracking of pure VGO and coprocessing of VGO with FPO and CGO with HDO at optimized conditions. 3-, 4- and 5-lump modeling using sequential approach for kinetic parameter estimation for different feedstocks. Predicted the gas oil, gasoline, dry gas, LPG and coke yields from the kinetic model. Abstract: A 5-lump kinetic model is proposed and validated to mean the catalytic cracking of pyrolysis oils with equilibrium fluid catalytic cracking catalyst (E-CAT) in an advanced cracking evaluation (ACE-R) FCC unit. In the present work a blend of fast pyrolysis oil (FPO) with vacuum gas oil (VGO); hydrodeoxygenated oil (HDO) with VGO; and VGO are used as raw materials. The kinetic modeling of lumped systems is carried out using a sequential approach. This approach decreased the number of simultaneous equations and hence estimated parameters. A 5-lump model, derived from 3- and 4-lumps, is used to represent the experimental data and used to estimate the kinetic constants and hence the yields of gasoline, LPG, dry gases, coke and feedstocks. In the sequential approach, the kinetic parameters have been estimated for a 3-lump model, and then the information is used to estimate the 4-lump parameters using a 4-lump model. Finally, the kinetic constants obtained from 4-lump are used to estimate the kinetic parameters for 5-lump model. A set of new experiments have been performed for catalytic cracking of pure VGO and coprocessing of FPO with VGO and HDO with VGO, by varying WHSV from 6 to 24 h −1, at a constant reaction temperature and C/O ratio of 530 °C and 5, respectively. The optimized process conditions were maintained to produce higher gasoline yield from VGO by catalytic cracking over equilibrium FCC catalyst. The process parameters obtained from lumped modeling, for catalytic cracking of pure VGO, have been compared with the kinetic parameters obtained from 4-lumped model available in the literature, and approximately 2% deviation were found in the products yields with respect to experimental data.